Study of the possibility of increasing the accuracy of measuring the concentration of particles of explosives by remote sensing methods - Romanyuk, V.A.; Starodubtsev, S.O.; Shapovalov, S.V. (Radiotekhnika, 2018)
Most of the existing methods for detection of explosives require sampling and sample preparation, whereas in the search for explosives, it is not always possible to contact the explosive device (ED). In this connection, the methods for remote detection of explosives by detecting their particles present in various quantities near or on the surface of the explosive are of particular interest. The difficulty of detecting such substances lies in the fact that, in addition to full-scale samples, they may be in the package. In addition, it often becomes necessary to detect a trace amount of hazardous substances on packages and contact surfaces. The purpose of the article is to study the possibility of improving the accuracy of lidar measurements of the concentration of particles of explosives, taking into account the width of the laser emission line and the absorption width of the molecule under study.